PERIPHERAL SETTLEMENTS OF CONCHOPATA URBAN CENTER, AYACUCHO - Pérez Calderón, Ismael (Arqueología y Sociedad, 2012)
Provides information on a variety of archaeological remains on the periphery of downtown Conchopata in Ayacucho, which is demonstrated not only a long occupation but an urban pattern with a background in local cultures prior to the Wari culture. He has logged more than 200 settlements distributed between 2500 and 4250 masl, whose ancient people made the most of natural resources in the area as well as the domain of geographic space, between the evidence include quarries, docks, canals, reservoirs, qochas, springs, settlements, rock art, caves, temples, huancas, ushnos, roads, etc., scattered on top of hills, creeks, hills, slopes, plains and deep gorges that make up the upper basin in southern highlands Huarpa central Peruvian Andes. Se presenta información sobre una variedad de restos arqueológicos ubicados en la periferia del centro urbano de Conchopata en Ayacucho, con lo que se demuestra no solo una larga ocupación sino un patrón urbano con antecedentes en culturas locales previas a la cultura Wari. Se tiene registrado más de 200 asentamientos distribuidos entre los 2500 y 4250 msnm, cuyos antiguos pobladores aprovecharon al máximo los recursos naturales de la zona así como el dominio del espacio geográfico, entre las evidencias destacan canteras, andenes, canales, reservorios, qochas, manantiales, centros poblados, arte rupestre, cuevas, adoratorios, huancas, ushnos, caminos, etc., dispersos en la cima de cerros, abras, montículos, laderas, planicies y profundidades de las quebradas que integran el curso superior de la cuenca del Huarpa en sierra sur central de los Andes peruanos.